PENSION SYSTEM REFORM IN KAZAKHSTAN BASED ON EXPERIENCE OF SINGAPORE - Kilibayev, Azamat; Sadykov, Mukhtar; Sultanbekova, Ayana (Nazarbayev University Graduate School of Public Policy, 2020)
In September 2019, the President of the Republic of Kazakhstan in his address to the Nation mentioned the possibility of using pension savings for buying a house or educational purposes and the reform of the pension system in general. The proposal was met by heated debates that mainly took place in the social media. However, lately, various proposals for reforming the pension system of the Republic of Kazakhstan have been vigorously discussed. The Singapore model is most often mentioned as a model of pension system and pension savings. One of the advantages of the Singapore model is the withdrawal of funds for purchase of housing, medicine or to pay for education. At the same time, different opinions are expressed regarding its feasibility and possible implementation in Kazakhstan. This study was aimed to analyze the issue of how applicable the Singaporean pension system for reforms in Kazakhstan. In general, this study is based on the qualitative analysis of primary and secondary data. As part of this work, 10 semi-structured interviews were conducted with a range of local and international experts. In addition, a survey of the population was carried out regarding the planned pension reform in Kazakhstan. To determine the opinion of the population and conduct an analysis, two cities were selected (one city with population incomes higher the average national level and a city with population incomes below the average national level) Nur-Sultan and in Ust-Kamenogrosk. Also, an in-depth analysis of secondary data regarding the impact on the planned reform of the main features of the functioning of the pension system of Kazakhstan, the state budget, demographic changes was carried out, as well as a comparison with the Singapore model. The findings of the study show public attitudes towards the President's initiative, and the findings of this research indicate that there are other important factors that will have some influence on the successful implementation of the Singaporean model. Based on the analysis and the results of the study, policy recommendations were given to the Government of Kazakhstan, as well as lessons we can draw from the experience Singapore’s retirement funding system to refine Kazakhstan’s pension and social protection systems.
Keywords: pension system; Singapore; state budget; efficiency; Kazakhstan; Singaporean model; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics